Welfare, employment, and hours of work - Axel Hall; Gylfi Zoega (University of Iceland, Institute of Economic Studies (IoES), 2020)
We use the Pissarides (2000) model to show how social benefits and increased bargaining power of workers can both cause high unemployment and short hours of work. While his matching model has been used to explain higher unemployment in Europe than in the United States, we augment it to account for another observation, which is the fewer hours of work in Europe. We derive an explicit wage curve with variable hours of work that captures wages (per hour) as a function of hours of work. This enables us to show why higher social benefits and greater bargaining power of workers have the dual effect of making workers prefer more leisure time and discouraging firms from offering vacancies.
Keywords: J63; J64; J65; 330; Job search; unemployment; working hours